The Constitutional Struggle for Religious Freedom: A Comparative Study of India and Indonesia - Neha Tripathi; Anubhav Kumar (The Constitutional Court of the Republic of Indonesia, 2022)
Constitutions tend to regulate the relationship between religious and state authorities. Before the rise of the modern state, it was difficult to make proper distinctions between law, religion and morality. With the emergence of Western liberalism, the concept of democracy and secularism gained newfound attention, becoming ingrained and in tune with modern constitutional frameworks. Establishing the relationship between state and religion is a thorny issue for constitution-makers. Opponents of constitutional recognition of religion view religion as a private matter, relating to personal beliefs and conscience. This paper studies the comparative constitutional frameworks of India and Indonesia in relation to the right to religious freedom. As vibrant democracies comprised of ethnically diverse populations, both India and Indonesia grapple with issues concerning religious majorities and minorities. In India, Hindus are the majority, then Muslims, Christians, Sikhs and Buddhists; whereas in Indonesia, Muslims are the majority, then Christians, Hindus and Buddhists. Both India and Indonesia have ratified the International Covenant on Civil and Political Rights. The judgments of the constitutional courts in these countries have prompted constitutional law scholars to analyze the status of constitutionally recognized freedom of religion and its enforceability. This article first studies the relationship between state and religion in the contemporary sphere, thereby engaging in a comparative study of the formation of constitutional provisions in relation to religious freedom in India and Indonesia. Second, it aims to establish the importance of religious freedom within a constitutional framework. Third, it will discuss the issues surrounding recognition and enforcement of religious freedom in India and Indonesia, as well as providing an analysis from the perspective of majoritarianism and religious intolerance. Fourth, it will analyze landmark judgments of the constitutional courts of India and Indonesia in formulating and establishing the basic tenets of religious freedoms in the two nations. The role of the judiciary and governmental institutions in dealing with issues of religious freedom remains a central question in democratic countries such as India and Indonesia. Keeping in mind the need for a more holistic study and contributing to the literature in this area, the authors will present a comparative analysis of religious freedom in both these nations for nuanced understanding of religious rights and their interplay with the respective constitutions.